2005
DOI: 10.1038/sj.bmt.1704946
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomised trial of amifostine cytoprotection in myeloma patients undergoing high-dose melphalan conditioned autologous stem cell transplantation

Abstract: Summary:In this prospective multicentre trial, 90 patients undergoing autologous stem cell transplantation (ASCT) were randomised to receive (n ¼ 43) or not receive (n ¼ 47) amifostine 910 mg/m 2 prior to melphalan 200 mg/m 2 . Patients were monitored for regimen-related toxicity, engraftment, supportive care, response and survival. Both groups underwent ASCT at a median of 8 months from diagnosis and were matched for disease characteristics, prior therapy and pre-ASCT disease responsiveness. Amifostine infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 29 publications
0
59
1
1
Order By: Relevance
“…7,15 Amifostine, a thiol-based cytoprotective agent, has been shown to reduce mucositis associated with high-dose melphalan. 8 Amifostine-treated patients had a reduction in the overall incidence of mucositis and less frequent severe mucositis. There was not, however, any difference in the utilization of parenteral nutrition or narcotics for pain relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,15 Amifostine, a thiol-based cytoprotective agent, has been shown to reduce mucositis associated with high-dose melphalan. 8 Amifostine-treated patients had a reduction in the overall incidence of mucositis and less frequent severe mucositis. There was not, however, any difference in the utilization of parenteral nutrition or narcotics for pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…6 The only approved agent for prevention of mucositis associated with high-dose therapy is palifermin, but several studies have shown that low-energy lasers or amifostine can reduce the incidence and severity of mucositis. 7,8 Additionally, there have been several reports of reduced oral mucositis in patients who kept ice chips in their mouth during infusional chemotherapy. 9,10 The scientific rationale for this approach is that cryotherapy leads to vasoconstriction and decreased blood flow to the oral cavity, which reduces the exposure of the buccal mucosa to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Higher frequency of severe mucositis in our study may possibly be a result of multiple factors including poor oral hygiene, prior extensive chemotherapy (33 patients received more than one regimen and, consequently, higher doses of steroids) and presence of progressive disease, renal failure and paraparesis in some patients. We attempted use of amifostine in 16 patients prior to highdose melphalan as suggested by Spencer et al; 24 grade III and IV mucositis was 43.8 and 31.3% compared with 38.1 and 33.3%, P ¼ NS among patients who did not receive amifostine. Recently, use of keratinocyte growth factor (pelifermin) has been associated with a reduced risk of mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, amifostine has been shown to reduce mucosal toxicity with associated complications in myeloma patients receiving high-dose MEL. 67,68 A human recombinant keratinocyte growth factor palifermin has reduced significantly the severity and duration of mucositis in patients with haematological malignancies receiving HDT. 69 Elderly patients receiving HDT might be optimal candidates for the use of these protective agents.…”
Section: Ways To Improve Outcomementioning
confidence: 99%